Perinatal Considerations in Women With Previous Diagnosis of Cancer. Issue 12 (December 2015) - Landa, Alejandro; Kuller, Jeffrey; Rhee, Eleanor
Abstract : As the average age that women have their first child increases and cancer therapies improve survival, obstetricians are more likely to care for pregnant women who have survived cancer. Managing these pregnancies can be challenging, as they may be associated with higher risks of maternal and neonatal morbidity and mortality. Different types of cancer require different types of intervention, including surgery, chemotherapy, radiation, or combinations of these. Prior cancer treatments therefore present different potential complications during pregnancy. Although for most women who survive cancer carrying a pregnancy does not seem to increase mortality rates, there are some associated neonatal morbidities. The most common perinatal complication associated with pregnancy after cancer is prematurity. Women who desire pregnancy after cancer survival should not be discouraged, but appropriate counseling and follow-up should be provided. Target Audience: Obstetricians and gynecologists, oncologists, family physicians. Learning Objectives: After completing this CME activity, the reader should be able to identify the most common malignancies during reproductive age, identify maternal morbidity associated with pregnancy after surviving cancer, and should be able to counsel women appropriately about neonatal outcomes in a pregnancy after cancer.